Educação infantil e educação musical: um estudo com pedagogas - Storgatto, Sabrina Silveira Spanavello (2011)
This research is linked to Line Arts Education and Research (LP4) from the Graduate Program in Education at Universidade Federal de Santa Maria (PPGE / UFSM) and aimed to understand how educators in an existing school in Santa Maria ( RS) conceive of music education in early childhood education and how they interact with the activities developed by scholars of Music Degree in conducting practices in their space. Specifically looked to see how teachers understand the music in their teaching activities and implement music education in their work, understand their needs in relation to music education in early childhood education and research about the interactions between teachers and trainees to promote music education in context of early childhood education. The study was a qualitative approach to case study. Data collection occurred in kindergarten classes, participated with observations in the context of performance of teachers and educators of the course trainees music Full Degree. Besides the observations was also used semi-structured interviews with teachers educators. The study is organized into five chapters. Initially I do my presentation and my approaches to music education in the context of childhood. Then frame the research institution by drawing a picture from my inserts there. Then I present insights into childhood in order to contextualize my eye this phase of development, and issues peculiar to childhood in the context of school education. Following step to the discussion of music education in early childhood education and then present the musical education I found in the context under study. I could see that the educators working in the institution have a vision of music as an area of knowledge, which is partly the presence of the trainees in their teaching contexts. However, in general, I realize that there is still need encouragement to those teachers looking for ways to articulate their teaching music education.